2014
DOI: 10.4046/trd.2014.76.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Combination of VNTR Typing for Discrimination of IsolatedMycobacterium tuberculosisin Korea

Abstract: BackgroundVariable-number tandem repeat (VNTR) typing is a promising method to discriminate the Mycobacterium tuberculosis isolates in molecular epidemiology. The purpose of this study is to determine the optimal VNTR combinations for discriminating isolated M. tuberculosis strains in Korea.MethodsA total of 317 clinical isolates collected throughout Korea were genotyped by using the IS6110 restriction fragment length polymorphism (RFLP), and then analysed for the number of VNTR copies from 32 VNTR loci.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…According to the Chinese genotyping handbook and protocol referenced literature ( Lee et al, 2014 ), 15 MIRU loci were selected in this study. The primer sequence and length of repeat units of each MIRU locus was shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Chinese genotyping handbook and protocol referenced literature ( Lee et al, 2014 ), 15 MIRU loci were selected in this study. The primer sequence and length of repeat units of each MIRU locus was shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Following an initial denaturation at 95°C for 10 min the PCRs were subjected to 40 thermocycles of 94°C for 60 s, 60°C for 60 s, and 72°C for 90 s. This was followed by a final extension at 72°C for 10 min. Positive and negative control reactions, in which PCR mixes were inoculated with 4 μL of boiled cells from the M. tuberculosis H37RV strain and sterile distilled water, respectively, were performed with each set of reactions ( Lee et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, we found recently that these K clusters showed different variable-number tandem repeat (VNTR) patterns ( 5 ). When we analyzed 52 M. tuberculosis isolates belonging to the K cluster in IS 6110 RFLP, which were isolated from different TB patients without any transmission links by Supply 24 VNTR loci ( 6 , 7 ), we found that the biggest VNTR cluster included 16 isolates (30.8%). This cluster had copy numbers 5, 3, 4, 9, 4, 4, 7, 2, 3, 3, 4, 2, 4, 3, 3, 2, 4, 5, 2, 4, 2, 3, 2, and 1 in VNTR loci 2163b, 0424, 1955, 4052, 3192, 4156, 2996, 0802, 3690, 4348, 2165, 0960, 2401, 1644, 3007, 0580, 2347, 2531, 2461, 0577, 2059, 3171, 0154, and 2687, respectively.…”
Section: Genome Announcementmentioning
confidence: 99%
“…In India, VNTR locus 1895 (QUB-1895) showed high-sequence polymorphism among the 91 isolates originating from 12 different regions in the country (Gutierrez et al, 2006). In Korea, besides the VNTR 3232, 3820, 4120, 3336, the loci of 2163b, 0424, 1955, 4052, 3192, 4156, 2996 and 2163a were also hyper variable based on the a result of VNTR typing of 317 M. tuberculosis strains isolated from Korea (Lee et al, 2014). Those regionspecific loci that yield high resolution power in certain areas are good complements to the classical VNTR method.…”
Section: Region Specified Vntr Panelsmentioning
confidence: 99%